Safety and Efficacy of Pancreaticoduodenectomy in Octogenarians - Huang, Yeqian; Damodaran Prabha, Ramesh; Chua, Terence C.; Arena, Jennifer; Kotecha, Krishna; Mittal, Anubhav; Gill, Anthony J.; Samra, Jaswinder S. (Frontiers in Surgery, 2021)
Backgrounds Pancreaticoduodenectomy (PD) remains the only hope of a cure in selected patients with pancreatic adenocarcinoma (PAC). With an aging population, there will be an increasing number of very elderly patients being diagnosed with PAC of whom a selected proportion would be suitable for PD. However, the literature on outcomes of elderly patients after PD remains ambiguous. Therefore, the aim of this study was to examine the safety and efficacy of PD in octogenarians with PAC. Methods A retrospective analysis of 304 patients with PAC undergoing PD. Patients were divided into two age groups using age of 80 years old as the cut-off. Results Overall mortality and major morbidity rates were 0.5% and 18.5% respectively. The octogenarian group had a higher rate of mortality (6.3%, n=1, p<0.001), a higher rate of major morbidity (37.5%, n=6, p=0.042) and a longer hospital stay (p=0.035). However, median survival of octogenarians was 15.6 months. Multivariate analysis showed age was not identified as a prognostic factor for major morbidity and overall survival. Conclusion Age alone should not be an exclusion criterion for consideration of PD. With careful selection, PD can be safely performed in octogenarians. Elderly patients should be referred to a specialised unit for an objective assessment to determine the suitability for this aggressive but potential curative approach.